Implementation of the Strategic Management of a Selected Multinational Company in the Selected Country - Lagosha, Olena; Pichanič, Mikuláš, 1942-; Kallookaran, Roberto; Vysoká škola ekonomická v Praze. Rektorát (2010)
In terms of the world globalization multinational companies are becoming more significant in the international trading system. One of the main conditions for opening the new market by a multinational company is an effective system of the strategic management. This thesis is aimed at analyzing the ways of LUKOIL operations in Ukraine. Moreover, the specific attention of the paper is devoted to the LUKOIL activities in the country. Taking into account all the particularities of the Ukrainian market, the conclusion provides clear evidence about the successful implementation of LUKOIL formulated strategy in Ukraine.
Vedoucí práce: Mikuláš Pichanič
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Rektorát, 2010
Rok obhajoby 2010
Keywords: international Business - Central European Business Realities [obor dipl. práce]; diplomové práce; master's theses